Ogilvie, Sheilagh. Controlling Contagion: Epidemics and Institutions from the Black Death to Covid - Arthi, Vellore (Journal of Economic Literature, 2026)
Vellore Arthi of University of California, Irvine, reviews “Controlling Contagion: Epidemics and Institutions from the Black Death to Covid” by Sheilagh Ogilvie. The Econlit abstract of this book begins: “Explores the past seven centuries of history to investigate how human societies dealt with epidemic disease, highlighting the features that have made institutional frameworks better at coordinating responses to epidemics and better at devising innovations to improve societal learning.”